Konsep Pariwisata Halal Berbasis Ekonomi Kreatif Dengan Sharia Regulation dalam Meningkatan Pendapatan dan Kesejahteraan Masyarakat di Sumatera Utara - Salman Nasution (Jurnal Riset Akuntansi dan Bisnis, 2021)
During a period of 5 (five) years, Malaysia is a country with a majority Muslim population visiting North Sumatra as a tourist destination, namely 15,243 people in 2018. Countries with a non-Muslim majority population also open up halal tourism business opportunities which are intended to accept Muslim tourists to the country by providing the facilities needed according to Islamic law. In the context of halal tourism in North Sumatra, it is important to have sharia regulation. This study uses the concept of the Qur'an, library methods, and studies of central and local government policies. The results of this study conclude that if halal tourism is based on a creative economy with the concept of Sharia Regulation applied by the government and society, it will positively increase the income and welfare of the people of North Sumatra.